Producer knowledge and perceptions of biochar for Eastern redcedar management - Han, Lori A.; Bray, Laura A.; Prigmore, Sadie; Busuioc, Lorena; Nairn, Robert (Frontiers in Sustainability, 2025)
Eastern redcedar (Juniperus virginiana), a conifer native to the eastern United States, poses a significant threat to the grasslands of the US. Great Plains due to its invasive characteristics and broad environmental tolerance. Current management strategies typically involve mechanical removal of established trees, generating substantial amounts of organic waste that is rarely repurposed. Converting this biomass into biochar presents a sustainable alternative, offering a value-added product that can enhance soil fertility, improve water retention, and sequester carbon—thereby addressing both ecological degradation and climate change while potentially creating new revenue streams for landowners. Despite these benefits, the practice of producing biochar from Eastern redcedar waste remains uncommon in the Great Plains. This study explores the factors contributing to limited adoption by assessing landowner knowledge, perceptions, and attitudes toward biochar, redcedar encroachment, and interest in using and/or producing biochar out of redcedar waste.